EDUCATIONAL TOURISM AS A CATALYST FOR ECONOMIC GROWTH: EVALUATING THE SIGNIFICANCE FOR VICTORIA AND AUSTRALIA - Edison (Universitas Hasanuddin, 2023)
This research delves into the transformative impact of Monash College's Consortium Program, a short-term international initiative for university students. Established in 2006, the program has become a linchpin in fostering cross-cultural understanding, attracting over 250 students from eight national universities in its eight-year span. Its strategic significance within the Victorian and Australian Tourism industry is underscored by its contribution to increased visitor numbers and revenue. The success is attributed to Monash College's adept implementation of a 7P's marketing mix strategy, strategically addressing product, price, place, promotion, people, partnership, and packaging. However, challenges loom, particularly in market expansion, as changing preferences among Asian students, especially from Japan, lean towards similar programs in the Philippines. To secure its market share, Monash College must adeptly navigate these shifts, reevaluate its promotional strategies, and overcome capacity limitations for sustained success in the evolving landscape of international education.